Refinement of the laminin alpha2 chain locus to human chromosome 6q2 in severe and mild merosin deficient congenital muscular dystrophy. Issue 2 (February 1997) - Naom, I S; D'Alessandro, M; Topaloglu, H; Sewry, C; Ferlini, A; Helbling-Leclerc, A; Guicheney, P; Weissenbach, J; Schwartz, K; Bushby, K; Philpot, J; Dubowitz, V; et al.
Abstract : About half of the children with classical congenital muscular dystrophy (CMD) show an absence in their skeletal muscle of laminin alpha2 chain, one of the components of the extracellular matrix protein, merosin. Linkage analysis implicated the laminin alpha2 chain gene (LAMA2) on chromosome 6q2, now confirmed by the discovery of mutations in the laminin alpha2 chain gene. We have further investigated the location of the LAMA2 locus on chromosome 6q2, using both linkage analysis in nine informative families and homozygosity mapping in 13 consanguineous families. Four of these families only had mild or moderate down regulation of laminin alpha2 chain expression and a milder phenotype; the rest had no protein or only a trace. Haplotype analysis in all the informative families, including those with partial laminin alpha2 expression, was compatible with linkage to chromosome 6q2. This observation expands the spectrum of the phenotype secondary to laminin alpha2 chain deficiency. Our results suggest that the LAMA2 locus is more centromeric than previously proposed. Recombinant events place the locus between markers D6S470 and D6S1620 in an interval of less than 3 cM.